Asymmetric Dearomative Halogenation of β‐Naphthols: The Axial Chirality Transfer Reaction. Issue 3 (24th October 2017) - Wang, Pengxin; Wang, Jie; Wang, Linqing; Li, Dan; Wang, Kezhou; Liu, Yuyang; Zhu, Haiyong; Liu, Xihong; Yang, Dongxu; Wang, Rui
Abstract: Axial naphthols are applied in asymmetric halogenative dearomatization reactions under simple and mild conditions in the work presented herein. The axial‐to‐central chirality conversion is efficiently accomplished, and the desired halogenated dearomatization products are obtained in high yields and enantioselectivities. By using commercially available halogenation reagents, the asymmetric fluorinative, chlorinative and brominative dearomatization reactions of axial naphthols derived from BINOLs are achieved. (BINOL=1, 1′‐Bi‐2‐naphthol) Abstract :